Organization, structure, and assembly of immunoglobulin heavy chain diversity DNA segments (The Rockefeller University Press, 1982)
We have identified, cloned, and sequenced eight different DNA segments encoding the diversity (D) regions of mouse immunoglobulin heavy-chain genes. Like the two D segments previously characterized (16, 17), all eight D segments are flanked by characteristic heptamers and nonamers separated by 12-bp spacers. These 10 D segments, and several more D segments identified but not yet sequenced, can be classified into three families based on the extent of sequence homology. The SP2 family consists of nine highly homologous D segments that are all 17-bp long and clustered in a chromosomal region of approximately 60 kb. The FL16 family consists of up to four D segments, two of which were mapped in the 5' end region of the SP2-D cluster. The two FL16D segments are 23 and 17 bp long. The third, the Q52 family, is a single-member family of the 10-bp-long DQ52, located 700 bp 5' to the JH cluster. We argue that the D-region sequences of the majority of heavy chain genes arise from these germline D segments by various somatic mechanisms, including joining of multiple D segments. We present a specific model of D-D joining that does not violate the 12/23-bp spacer rule.